Efeito da sazonalidade nos níveis de atividade física em adultos - Bressan, Ana Weigert (Universidade do Vale do Rio do Sinos, 2008)
There are no consistent findings about the effect of weather and season changes on the physical activity levels. We conducted a study to evaluate seasonal effects on physical activity levels among adults living in Porto Alegre and metropolitan region, Southern Brazil. The study design was longitudinal with a convenience sample of 120 adults, aged 20 to 69. Visits were carried out in two periods of the year 2007: summer and winter. Physical activity was evaluated using the leisure-time and transport-related physical activity sections of the International Physical Activity Questionnaire (IPAQ). Socioeconomic and demographic characteristics were obtained by standardized questionnaires. Analyses were stratified by gender, age, education, socioeconomic and Body Mass Index (BMI). A total of 120 people were interviewed, 71% were women. Most people (59%) were in the 20-40 years age group, 61% had more than 12 years of education and belonged to A and B socioeconomic levels (83%). Overweight / normal weight ratio was 1
Keywords: efeito sazonal; IPAQ; atividade física; seasonal effects; physical activity; Ciências da Saúde